Crosslinked Urethane Doped Polyester (CUPE) Biphasic Scaffold: Potential for In vivo Vascular Tissue Engineering - Dey, Jagannath (2010)
In vivo tissue engineering uses the body as a bioreactor for tissue regeneration, thus placing stringent requirements on tissue scaffolds which should be mechanically robust for immediate implantation without a long in vitro cell culture time. In addition to mechanical strength, vascular grafts fabricated for in vivo tissue engineering approach must have matching mechanical properties to the target tissues to avoid compliance mismatch, which is one of the reasons for graft failure. We recently synthesized a new generation of strong and elastic biodegradable crosslinked urethane-doped polyesters (CUPE) to address the challenge of developing soft, elastic yet strong biodegradable polymers. This study evaluated the tensile strength, burst pressure and suture retention of CUPE biphasic scaffolds to determine if the scaffolds met the requirements for immediate implantation in an in vivo tissue engineering approach. Additionally, we also examined the hemocompatibility and inflammatory potential of CUPE to demonstrate its potential in serving as a blood-contacting vascular graft material. Tensile strength of CUPE biphasic scaffolds (5.02±0.70 MPa) was greater than native vessels (1.43±0.60 MPa). CUPE scaffolds exhibited tunable burst pressure ranging from 1500 mmHg to 2600 mmHg, and adequate suture retention values (2.45±0.23 N). CUPE showed comparable leukocyte activation and whole blood clotting kinetics to poly(L-lactic acid) PLLA. However, CUPE incited a lesser release of inflammatory cytokines and was found to be non hemolytic. Combined with the mechanical properties and previously demonstrated anti-thrombogenic nature, CUPE may serve as a viable graft material for in vivo blood vessel tissue engineering.